The Effect of Collaborative Learning Model on Improving Science Concept Understanding among Prospective Elementary School Teachers at Lambung Mangkurat University Student - Mubarok Mubarok; Rianty Yulandra; Bagus Aulia Iskandar (LP. Ma'arif Janggan Magetan, 2025)
This study aims to describe the implementation of the collaborative learning model toward improving students’ conceptual understanding in science courses. This research employed a quasi-experimental design with a pretest–posttest control group. Data were analyzed using gain scores to determine the effectiveness of the model. The results showed that the collaborative learning model had a positive and significant effect on students’ conceptual understanding in the Advanced Science course. The average pretest score in the control class was 46.11, while in the experimental class it was 51.81. After the implementation of the collaborative learning model, the posttest scores increased to 68.56 in the control class and 80.11 in the experimental class. The gain score in the control class was 0.01, while in the experimental class it was 0.06, indicating a higher improvement in conceptual understanding among students taught using the collaborative learning model. These findings demonstrate that collaborative learning can effectively enhance students’ mastery of scientific concepts through peer interaction, discussion, and shared learning responsibility. The results imply that this model can be an effective alternative for improving science learning outcomes in teacher education programs.